UPAYA MENINGKATKAN HASIL BELAJAR GERAK DASAR LARI MELALUI PERMAINAN BOLA WARNA PADA SISWA KELAS II SD NEGERI GETAS 1 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study to determine the i mprovement of learning outcomes run the basi c mot i on using colorball game on t he second grade students of SD Negeri 1 District Wonosalam Brittle Demak regency.Impl ementat ion of classroom action research was conducted in two cycles where each cycl e consists of f ourstages: planning, action, observation (observation), and reflection. Methods of data coll ect ion in t his studyusing t he methods of document ation, observat ion, and quest ionnaires. Analysis of research data wi t hdescript ive anal ysis percentage. Based on the survey result s revealed that t he learning outcomes of basic motionrun in cycle 1 in the cat egory at 72.72% complete and on cycle 2 increased to 95.45%, the activity of st udents incycl e 1 of 83 (very good), whil e in t he second cycle of 92 (very good), the value of the average st udent in cycl e 1was 79.8 and in cycl e 2 was 81.2. Overall value obtained for each aspect has increased. The concl usi on of thestudy is t hrough color ball games can improve learning outcomes run t he basic motion.